Pengaruh Kedisiplinan Terhadap Hasil Belajar Santri Di Pondok Pesantren Amanatul Ummah Surabaya - Rohmatul Maula, Virda; Yuliastutik; Badriyah, Laila (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This research aims to analyze the influence of discipline on the learning outcomes of students at the Amanatul Ummah Islamic Boarding School in Surabaya. Discipline is an important factor in the educational process, especially in the context of Islamic boarding schools, where strict rules and regulations are implemented as part of character building for students. This research uses a quantitative approach with a survey method involving 55 students as respondents. Data was collected through a questionnaire designed to measure the level of discipline and learning outcomes, which are represented by the students' average academic scores. The results of the linear regression analysis show that there is a significant influence of discipline on student learning outcomes with a regression coefficient of 1.279, which shows that increasing discipline contributes positively to improving learning outcomes. High student discipline is related to consistent attendance, active involvement in teaching and learning activities, and compliance with Islamic boarding school rules, all of which contribute to better academic achievement. This research concludes that discipline is one of the main determinants in achieving student learning outcomes at Amanatul Ummah Surabaya. These findings provide important implications for Islamic boarding school managers to continue to encourage and strengthen a culture of discipline among students in order to improve the quality of education. Suggestions are given to Islamic boarding schools to integrate more structured and effective disciplinary development programs to support the academic success of students.